Three Arguments to Support International Binding Treaty on Business and Human Rights - Surya Oktaviandra (Jurnal HAM, 2022)
The development of the promotion and protection of human rights, in general, has been gladdening. However, in instances where human rights are affected by business activity, efforts to uphold them meet certain obstacles. This is exacerbated when the business activity involves a complex and international dimension in it—i.e., in the case of multinational enterprises. This paper provides three arguments to support the establishment of international binding treaty on business and human rights. It examines the current Corporate Social Responsibility platform, state responsibility to protect human rights, and also the importance and benefits of legally binding treaty. This research found that the implementation of the current CSR platform fails to prevent business harm to human rights. Therefore, state responsibility is fundamental in this matter and should be enhanced by the duty to establish an international treaty. A legally binding treaty is important to protect human rights from irresponsible business activity and can be beneficial and relevant to the interest of parties involved in business and human rights.